Optimizing Regional Development Banks’ Role: Financial Intermediation and Inclusion for Economic Growth - Evi Sistiyarini; Dewi Ayu Wulandari; Ririn Poerwanti (Target : Jurnal Manajemen Bisnis, 2026)
Regional Development Banks (RDBs) play a pivotal role in fostering national economic growth through financial intermediation and expanding financial inclusion. Nonetheless, RDBs face both challenges and opportunities in extending credit to the productive sector and enhancing access to financial services for underserved communities. This study aims to examine how optimizing RDB functionality can enhance its contribution to regional economic development. The methodology employed in this research is panel data regression analysis, incorporating eight independent variables, namely Loan-to-Deposit Ratio, Non-Performing Loans, Third-Party Funds, Operating Expense Ratio to Operating Income (BOPO), Return on Equity (ROE), Bank Size, Financial Inclusion, and Inflation, with economic growth serving as the dependent variable. Data were sourced from the financial reports of RDBs, the Financial Services Authority (OJK), and the Central Statistics Agency (BPS), covering 38 RDBs and 23 banks. The findings indicate that Third-Party Funds, Non-Performing Loans, and Inflation positively and significantly influence economic growth. Conversely, Bank Size shows a negative, significant impact. The Loan-to-Deposit Ratio exhibits a positive but not statistically significant effect, whereas ROE, BOPO, and Financial Inclusion have negative and significant effects on economic growth. These results offer critical insights for optimizing the intermediation performance of RDBs in supporting sustainable economic development, particularly at the regional level, thereby providing a foundation for broader national economic advancement.